Abnormalities in Hyperpolarized 129Xe Magnetic Resonance Imaging and Spectroscopy in two Patients with Pulmonary Vascular Disease. (March 2016) - Dahhan, Talal; Kaushik, Shiv S.; He, Mu; Mammarappallil, Joseph G.; Tapson, Victor F.; McAdams, Holman P.; Sporn, Thomas A.; Driehuys, Bastiaan; Rajagopal, Sudarshan
The diagnosis of pulmonary vascular disease (PVD) is usually based on hemodynamic and/or clinical criteria. Noninvasive imaging of the heart and proximal vasculature can also provide useful information. An alternate approach to such criteria in the diagnosis of PVD is to image the vascular abnormalities in the lungs themselves. Hyperpolarized (HP) 129 Xe magnetic resonance imaging (MRI) is a novel technique for assessing abnormalities in ventilation and gas exchange in the lungs. We applied this technique to two patients for whom there was clinical suspicion of PVD. Two patients who had significant hypoxemia and dyspnea with no significant abnormalities on computed tomography imaging or ventilation-perfusion scan and only mild or borderline pulmonary arterial hypertension at catheterization were evaluated. They underwent HP 129 Xe imaging and subsequently had tissue diagnosis obtained from lung pathology. In both patients, HP 129 Xe imaging demonstrated normal ventilation but markedly decreased gas transfer to red blood cells with focal defects on imaging, a pattern distinct from those previously described for idiopathic pulmonary fibrosis or obstructive lung disease. Pathology on both patients later demonstrated severe PVD. These findings suggest that HP 129 Xe MRI may be useful in the diagnosis of PVD and monitoring response to therapy. Further studies are required to determine its sensitivity and specificity in these settings.